Tracing Sediment Sources in a Subtropical Agricultural Catchment of Southern Brazil Cultivated With Conventional and Conservation Farming Practices. (25th January 2017) - Le Gall, Marion; Evrard, Olivier; Dapoigny, Arnaud; Tiecher, Tales; Zafar, Mohsin; Minella, Jean Paolo Gomes; Laceby, J. Patrick; Ayrault, Sophie
Abstract: In Brazil, agricultural expansion has increased soil erosion and sediment supply to waterways. As elevated sediment loads often degrade freshwater environments, sediment fingerprinting techniques are increasingly used to identify the sources supplying sediment to riverine and lacustrine environments. In this study, the contribution of various soil types to sediment was investigated in the Guaporé catchment (2, 032 km 2 ) in southern Brazil. Soil samples ( n  = 75) were collected to characterise five soil types: Ferralsols ( n  = 26), Nitisols ( n  = 13), Acrisols ( n  = 8), Leptosols ( n  = 6) and Luvisols ( n  = 22). Sediment samples ( n  = 7) were collected in a trap installed at the catchment outlet. Sediment source contributions were modelled according to soil types with elemental geochemistry and 87 Sr/ 86 Sr ratios. 87 Sr/ 86 Sr ratios, K, Ti, Co, As, Ba and Pb were selected as the optimal suite of properties discriminating between soil types. Sediment samples were modelled to mainly originate from downstream Acrisols [mean 41%, standard deviation (SD) 2%], Leptosols (mean 34%, SD 4%) and Luvisols (mean 17%, SD 4%). In contrast, contributions of upstream Ferralsols (mean 4%, SD 2%) and Nitisols (mean 4%, SD 6%) were low. These results suggest that soils found in lower parts of the catchment, cultivated with conventional agriculture on steep slopes, were the main source of sediment to the river network. In contrast, soils found in upper parts of the catchment, cultivated with soybean under direct sowing, were less eroded or deposited before reaching the sediment sampling location at the outlet. These findings demonstrate that the management of local and degraded soil sources is important for reducing sediment loads. Copyright © 2016 John Wiley & Sons, Ltd.